2013
DOI: 10.1016/j.jnutbio.2012.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Holocarboxylase synthetase interacts physically with euchromatic histone-lysine N-methyltransferase, linking histone biotinylation with methylation events

Abstract: interacts physically with euchromatic histone-lysine N-methyltransferase, linking histone biotinylation with methylation events" (2013 AbstractHolocarboxylasesynthetase (HCS) catalyzes the binding of the vitamin biotin to histonesH3 and H4, thereby creating rare histonebiotinylation marks in the epigenome. These marksco-localize with K9-methylated histone H3 (H3K9me), an abundant gene repression mark. The abundance of H3K9me marks in transcriptionally competent loci decreases when HCS is knocked down and when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 50 publications
3
30
0
Order By: Relevance
“…This observation goes beyond our previous studies, which suggest that HLCS interacts physically with the core histones H3 and H4 and the histone methyltransferase EHMT-1. 8,17 The interactions between HLCS and histones may account for the binding of HLCS to chromatin, but does not explain the punctuate pattern of HLCS localization that was observed in previous studies, 6,7 simply because core histones can be found in all nucleosomes in chromatin. Likewise, the interactions between HLCS and EHMT-1 are unlikely to mediate the initial positioning of HLCS, based on previous observations that HLCS knockdown causes a loss of EHMT-1 dependent H3K9me marks.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This observation goes beyond our previous studies, which suggest that HLCS interacts physically with the core histones H3 and H4 and the histone methyltransferase EHMT-1. 8,17 The interactions between HLCS and histones may account for the binding of HLCS to chromatin, but does not explain the punctuate pattern of HLCS localization that was observed in previous studies, 6,7 simply because core histones can be found in all nucleosomes in chromatin. Likewise, the interactions between HLCS and EHMT-1 are unlikely to mediate the initial positioning of HLCS, based on previous observations that HLCS knockdown causes a loss of EHMT-1 dependent H3K9me marks.…”
Section: Discussionmentioning
confidence: 88%
“…In contrast, when DNMT1 was incubated lysine-9 methyltransferase EHMT-1. 8,17 Lysine-9 methylated histone H3 (H3K9me) is an abundant gene repression mark and EHMT-1 is one of the enzymes capable of creating this mark. 18 HLCS physically interacts with EHMT-1 and catalyzes the biotinylation of lysine (K) residues in EHMT-1, which strengthens the interactions between the proteins in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations